2 Heart failure virtual consult: technology to improve heart failure care in the community. (5th October 2017) - James, S; Gallagher, J; Keane, C; Fitzgerald, A; Travers, B; Ledwidge, M; McDonald, K
Abstract : Background: The St Vincent's University Hospital Heart Failure Unit in Dublin, Ireland had been providing heart failure virtual consult (HFVC) service for primary care physicians (PCPs) since May 2014. The HFVC service utilises teleconferencing technology to mentor and educate the PCPs on management of heart failure (HF) patients. The purpose of this analysis is to report on the single centre experience and outcome of HFVC. Methods: Consecutive 132 HF consultations from May 2014 till November 2016 were included. The consultations were categorised as new diagnostic, emerging deterioration, or therapeutic cases. The demography, medical diagnoses, and medications were recorded. The outcome were measured as general intervention outcome, final diagnoses in the new diagnostic cases and metric of patient convenience. Results: In 31 months, there were 73 new diagnostic (49.3% male; median age 78 [72 : 82] years), 35 emerging deterioration (60% male; median age 81.5 [76 : 86] years) and 24 therapeutic (54.2% male; median age 82 [71 : 86] years) cases. The full demography, medical diagnoses, medications and metric of patient convenience were described in detailed in Table 1 and 2. The general intervention outcomes of the HFVC were described in Figure 1. In new diagnostic cases, 25 (34.2%) were confirmed HF, 27 (37.0%) were confirmed not HF, and 21 (28.8%) were still indeterminate HF. Conclusions: HFVC service is a feasible model in providing specialist care for HF patients in the community. HFVC could save time and travel distance for HF patients by receiving treatment by their PCPs. The HFVC service help to diagnose possible HF early and guide PCPs to enrol guideline-based therapy early.